Gastrin-releasing peptide: predictor of castration-resistant prostate cancer? - Heinrich, Elmar; Probst, Kai Alexander; Michel, Maurice Stephan; Trojan, Lutz (The prostate, 2011)
BACKGROUND Neuroendocrine (NE) cells of the prostate are known to be androgen-independent and NE peptides like gastrin-releasing peptide (GRP) or neuron-specific enolase (NSE) can stimulate growth in a paracrine manner, and this is thought to be one of the escape mechanisms in castration-resistant prostate cancer (CRPCa). In a longitudinal study, we investigated the development of the NE serum factors GRP, NSE, and chromogranin A and their correlation with prostate-specific androgen (PSA) during hormonal treatment. MATERIALS AND METHODS Thirty two patients, with histology-proven, localized or metastatic prostatic carcinoma (PCa), who were undergoing therapy with LHRH analogue or a combination of LHRH analog and peripheral androgen blockade, took part in the study. In addition, eight healthy volunteers were each tested twice for serum GRP to elicit a “physiological” standard value. Blood samples were taken periodically from each patient within an 18-month time frame. RESULTS We defined the standard value for GRP in the healthy participants as 0.852 ng/ml (mean + 2 SD) and observed that the GRP values for patients with PCa were significantly higher (P = 0.034). There was a positive correlation between PSA and GRP in patients with biochemical failure. CgA correlated with PSA development in the CRPCa patients. NSE values rose steadily over the study period, but with no correlation to PSA. CONCLUSION Our data confirm that NE factors are elevated during hormonal treatment of prostate cancer. GRP is higher in PCa patients undergoing androgen deprivation therapy and is possibly involved in the initiation of hormonal escape in PCa. Prostate 71:642-648, 2011. © 2010 Wiley-Liss, Inc.